PROSPECTIVE MATHEMATICS TEACHERS’ MATHEMATIZATION COMPETENCIES IN SOLVING WORD PROBLEMS - Hamidah, Dewi; Susiswo, Susiswo; Susanto, Hery; Osman, Sharifah (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Mathematization competencies among prospective teachers, focusing on their ability to construct and communicate mathematical arguments, are crucial for effective mathematics education. This exploratory study aimed to produce qualitative-descriptive data on prospective teachers' competencies of mathematization in teacher education programs. The study employs word problems based on everyday-life problems that are solved by the mathematization process and assessed based on three indicators of mathematization competencies. The data were collected from three groups of prospective teachers in the first, third, and fifth semesters, respectively, in the mathematics education study program at a public University in Kediri, Indonesia. The findings revealed that while all prospective teachers demonstrated basic skills in identifying assumptions and organizing problems, fifth-year students exhibited better abilities in mathematical argumentation, particularly in generalizing mathematical problems. These advanced abilities included the formulation, analysis, and presentation of proficient mathematical arguments, indicating a deeper understanding and mastery of mathematization that developed progressively throughout their education. The results of this study underscore the importance of sustained and structured learning experiences in mathematics teacher education programs to foster higher-order mathematical competencies. This study enriches the mathematics education literature by illustrating the growth of argumentation skills in mathematization among prospective teachers, highlighting the need for educational curricula that emphasize these advanced skills.